Poof! - O'Brien, John (Honesdale, Pa. : Boyds Mills Press, 2005)
Two lazy wizards resort to all sorts of tricks in order to get out of doing simple chores around the house.
86390
Keywords: Wizards -- Juvenile fiction; House cleaning -- Juvenile fiction; Wizards -- Fiction; House cleaning -- Fiction